/(b+c-a)=y/(c+a-b)=
已知x\/(b+c-a)=y\/(c+a-b)=z\/(a+b-c),求证(b-c)x+(c-a)y+(a-b)z=0
1个回答
相关问题
-
已知a(y-z)+b(z-x)+c(x-y)=0,求证:(x-y)/(a-b)=(y-z)/(b-c)=(z-x)/(c
-
已知:a/(z-2y+x)=b/(x-2z+y)=c/(y-2x+z),a+b+c≠0.求证:(a+b)(b+c)(c+
-
x-y/a=y-z/b=z-x/c,x,y,z互不相等,求证:a+b+c=0
-
已知x/y+z=a,y/x+z=b,z/x+y=c求a/a+1+b/b+1+c/c+1
-
若x/(a+2b+c)=y/(a-c)=z/(a-2b+c),且a,b,c,x,y,z均不为0,求证a/(x+2y+z)
-
已知x=2a-b-c,y=2b-c-a,z=2c-a-b,求x(b-c)+y(c-a)+z(a-b)的值
-
已知x+y=z,则x(a+b-c)-y(c-a-b)-z(b-c+a)的值为
-
已知x.y.z均为实数x+y+z≠0 a=x/y+z b=y/z+x c=z/x+y那么a/a+1+b/b+1+c/c+
-
已知a/x + b/x + c/x =0,x/a + y/b + z/c =1 ,求证 x·x / a·a + y·y
-
已知x=a/(b+c),y=b/(c+a),z=c/(a+b),且a+b+c不等于0,求x/(1+x)+y/(1+y)+